Improving Food Literacy and Access Among Young Adult Cancer Survivors: A Cross-Sectional Descriptive Study. Issue 2 (13th March 2022) - Alexander, Gina K.; Bashore, Lisa; Brooks, Vicki
Abstract : Background: The links between nutrition and chronic disease are well established, but consumption of fruits and vegetables is low among young adult childhood cancer survivors (YACS) worldwide. Ensuring equitable access to fresh produce is a significant, persistent public health challenge. Objective: The purposes of this report are to describe patterns of access to fresh produce, daily intake of fruits/vegetables, and nutrition education preferences among a sample of YACS and to highlight early development of a mentored gardening intervention. Methods: A cross-sectional descriptive study design was used to assess dietary intake, access to fruits/vegetables, and preferences for nutrition education among 124 YACS through a comprehensive cancer survivorship program in a large pediatric cancer center. Results: Most participants (71.8%) live more than 10 minutes' walking distance from a supermarket, and 88.7% do not meet the recommended daily intake of 5 or more servings of fruit and vegetables. A total of 91% of participants express that nutrition is important, and 81.5% desire dietary improvement. Most (78.2%) are likely to use either their computer or cell phone for nutrition content. To establish healthy nutrition habits, many seek the support of a nutritionist (63.7%) or another survivor (41.9%). Conclusions: Study findings underscore the need for advocacy to support equitable access to fresh produce and technology-enhanced nutrition education among YACS. Implications for Practice: To improve access to fresh produce and food literacy among YACS, providers can collaborate with community stakeholders to build capacity for sustainable, technology-enhanced, and mentored gardening interventions at the individual, family, and community level.